A method for the characterization of fans down to zero speed and analysis of bypass reverse flow during ground start - Roig Tió, Ferran; Azamar, Hasani; Pachidis, Vassilios (Global Power and Propulsion Society, 2021)
The subidle operation of turbofan engines for ground start and relight has been of interest since the advent of the turbofan engine architecture and more so in recent years. Apart from being able to start the engine on the ground quickly, a significant challenge in the engine design exercise is to demonstrate the capability of inflight relight under windmill conditions. This becomes more critical for very high bypass ratio (VHBR) turbofans where the core mass flow rates are even lower due to the large bypass ratios. To test the ability of an engine to relight, it is necessary to know the component subidle performance characteristics, which are normally unknown. Over the years, substantial and significant work has been published on the generation of meanline methods to predict the axial flow core compressor subidle performance; however, there is practically no previous research published on standard tools for subidle regime in axialflow fans. In this investigation, the appropriateness of a loworder method based on interpolation is examined for the subidle performance characterization of the fan. It is shown that although results for the fan root may lack sufficient accuracy, the obtained solutions for the fan tip match CFD predictions very well. Also, a numerical investigation is carried out to study the effect of reverse flow through the bypass duct during ground start. In general, it is shown that reverse bypass duct flow during ground start has very little effect on core entry engine flow.